Anti-fog self-cleaning titanium dioxide composite sol coating and preparation method thereof
By using titanium dioxide composite sol coating on the plastic surface and combining the sol-gel method, the problems of poor adhesion and insufficient hydrophilicity of titanium dioxide coating on the plastic surface are solved, and super hydrophilic anti-fog effect and stability are achieved, avoiding The use of high temperature and corrosive reagents is suitable for a variety of materials.
Patent Information
- Application Number
- CN202411393487.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2024-12-24
AI Technical Summary
The prior art titanium dioxide coatings used for anti-fog treatment on plastic surfaces have poor adhesion, insufficient hydrophilicity, and the need for high temperature and corrosive organic reagents, resulting in complex operation and unweather resistance.
Using titanium dioxide composite sol coating, the film is formed by spraying or drop coating on the surface of the plastic substrate, combining titanium dioxide and silica precursor sol, and preparing by sol gel method, avoiding ultraviolet pretreatment and high-temperature calcination, and improving the coating Adhesion and weather resistance.
It achieves super hydrophilic and anti-fog effect, the coating is stable and not easy to fall off, and is suitable for a variety of material surfaces, reducing production costs and process complexity.
Smart Images

Figure CN119177035A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of chemical technology, and in particular to an anti-fog self-cleaning titanium dioxide composite sol coating and a preparation method thereof. Background Art
[0002] Glass and transparent plastics play an important role in our daily lives, but these transparent materials themselves have the problem of fogging. Saturated water vapor will condense on their surface and then form small fog droplets, which will greatly reduce the light transmittance of the material and cause problems in aesthetics, hygiene, safety, etc. For example, fogging of car windshields on rainy days will affect driving safety; fogging of food wrap will affect the appearance and preservation of food; fogging of agricultural films will cause seedlings to burn, and fog droplets will cause crop seedlings to rot. Therefore, a stable anti-fog coating has very important application value in actual life and production.
[0003] At present, researchers have developed various anti-fog methods, such as hydrophilic organic coatings, surfactants and other methods, but these organic coatings often face the problem of reduced effectiveness after the loss of hydrophilic components. Inorganic titanium dioxide is widely used in anti-fog self-cleaning treatment of glass surfaces due to its light-induced super hydrophilicity. However, titanium dioxide coatings usually require thermal curing to promote the crystallization of titanium dioxide, thereby having better photocatalytic properties. Titanium dioxide coatings currently used on plastic surfaces often face problems such as poor adhesion and insufficient hydrophilic stability. At the same time, for plastic surface treatment, a milder treatment method is needed to avoid corrosive organic reagents and high temperature conditions.
[0004] Therefore, a milder method is needed to prepare anti-fog coatings. Summary of the invention
[0005] The present invention aims to solve the problems of complex anti-fog treatment operation, poor weather resistance, easy water solubility, and poor wear resistance, and provides an anti-fog self-cleaning titanium dioxide composite sol coating and a preparation method thereof. The titanium dioxide composite sol is used to achieve anti-fog self-cleaning treatment on the surfaces of various materials. Compared with the current anti-fog treatment method, the coating prepared by the present invention does not require ultraviolet pre-treatment to achieve super-hydrophilic anti-fog, and does not require high-temperature calcination and other conditions, so it is more practical. Compared with the anti-fog treatment method of the hydrophilic polymer coating, the present invention has strong water resistance, good weather resistance, good adhesion on the surfaces of various materials, is not easy to fall off, and has a stable anti-fog effect.
[0006] The present invention provides an anti-fog self-cleaning titanium dioxide composite sol coating, wherein the titanium dioxide composite sol is pulled or directly sprayed or dripped or rolled or spin-coated on the surface of a plastic substrate to form a film, and the titanium dioxide composite sol coating is obtained after the solvent evaporates;
[0007] The titanium dioxide composite sol comprises a titanium dioxide precursor sol and a silicon dioxide precursor sol in a molar ratio of (3-7): (3-7), and the solid content is: 0.8-8%;
[0008] The plastic substrate includes any one of the following: glass sheets, eyeglass lenses, polyvinyl chloride films, agricultural polyethylene films, commercial greenhouse films, polycarbonate films, and polyethylene terephthalate films.
[0009] The anti-fog self-cleaning titanium dioxide composite sol coating of the present invention is preferably a titanium dioxide precursor sol composed of TiO 2 Nanocrystal composition.
[0010] The anti-fog self-cleaning titanium dioxide composite sol coating of the present invention, as a preferred embodiment, or the titanium dioxide composite sol comprises a titanium dioxide precursor sol and a metal oxide, and the metal oxide is zirconium dioxide or aluminum oxide;
[0011] Alternatively, silicon dioxide or an organic intermediate layer is added to the titanium dioxide composite sol to improve the adhesion of the coating on the plastic substrate, and the organic intermediate layer is an organic silicon film or a polyurethane film.
[0012] The present invention provides a method for preparing an anti-fog self-cleaning titanium dioxide composite sol coating, comprising the following steps:
[0013] S1, using tetraethyl silicate, HNO 3 , deionized water, and anhydrous ethanol are prepared in a molar ratio of 1:0.005-0.1:3-10:5-20 to obtain a silica sol, and the silica sol is aged at 50° C. for 1-7 days to obtain a silica precursor sol;
[0014] S2, using titanium compound, deionized water, nitric acid, anhydrous ethanol and a stabilizer to prepare a titanium dioxide mother solution, wherein the molar ratio of the titanium compound, deionized water, stabilizer and nitric acid is 1:0.5-10:0.1-0.5:0.1, and anhydrous ethanol is used to control the concentration of the titanium compound in the titanium dioxide mother solution;
[0015] The titanium dioxide mother liquor was added dropwise into deionized water under stirring conditions, and the final molar ratio of deionized water to titanium compound was controlled to be 50-400, and then the mixture was continuously heated under reflux and stirred for 12 hours to generate TiO 2 The particles are crystallized, and then the water is removed by exchange with anhydrous ethanol and diluted to a specified concentration to obtain a titanium dioxide precursor sol;
[0016] The titanium dioxide precursor sol and the titanium dioxide precursor sol are mixed and stirred at a molar ratio of (3-7): (3-7) to obtain a titanium dioxide composite sol, and anhydrous ethanol is used as a diluent to adjust the solid content of the titanium dioxide composite sol to 0.8-8%;
[0017] S3. Clean and dry the plastic substrate and then treat it with vacuum plasma. Form a film by pulling, direct spraying, dripping, rolling or spin coating. After the solvent evaporates, a coating is obtained. After heating and curing at 40 to 80° C., a titanium dioxide composite sol coating is obtained.
[0018] The method for preparing an anti-fog self-cleaning titanium dioxide composite sol coating of the present invention is preferably as follows: in step S1, when preparing the silica sol, tetraethyl silicate and half volume of anhydrous ethanol are first mixed evenly, and stirred under magnetic force for 20 minutes to obtain a tetraethyl silicate anhydrous ethanol mixed solution; then HNO 3 , deionized water and the other half volume of anhydrous ethanol are mixed evenly, and then added dropwise into the tetraethyl silicate anhydrous ethanol mixture at room temperature, and the mixture is stirred continuously in a sealed glass bottle for 6 hours to obtain a silica sol.
[0019] The method for preparing an anti-fog self-cleaning titanium dioxide composite sol coating of the present invention is preferably such that in step S2, the titanium compound is tetrabutyl titanate or isopropyl titanate or titanium tetrachloride or titanyl sulfate, the stabilizer is acetylacetone, and the concentration of the titanium compound in the titanium dioxide mother liquor is 0.4M;
[0020] First, the titanium compound and half volume of anhydrous ethanol are mixed evenly, and acetylacetone is added at the same time. After magnetic stirring for 20 minutes, the other half volume of anhydrous ethanol, water, and nitric acid mixture are added dropwise under stirring conditions; stirring is continued for 6 hours after the addition, and then aged at room temperature for 2 days to obtain a titanium dioxide mother solution;
[0021] The heating reflux temperature is 90-100°C;
[0022] The method of exchanging with anhydrous ethanol to remove water is as follows: first, part of the water is removed by rotary evaporation, so that TiO 2 The sol volume was reduced to 20% of the original volume, and then it was dissolved with anhydrous ethanol, and the process of removing water by rotary evaporation was repeated 3 times;
[0023] The specified concentration is: titanium dioxide solid content 2 to 10%;
[0024] The titanium dioxide precursor sol is mixed with the titanium dioxide precursor sol and then diluted with anhydrous ethanol to make the solid content of the titanium dioxide composite sol be 0.8-8%.
[0025] The method for preparing an anti-fog self-cleaning titanium dioxide composite sol coating of the present invention is preferably such that in step S3, the vacuum plasma treatment time is 5 minutes and the power is 200 W; the contact angle of the glass substrate after the vacuum plasma treatment is less than 40°;
[0026] The coating curing conditions are: leaving at room temperature for 24 hours.
[0027] The method for preparing an anti-fog self-cleaning titanium dioxide composite sol coating described in the present invention is, as a preferred embodiment, in step S3, the spraying pressure is 0.3MPa, the spraying distance is 10-20cm, 2-10 cycles of spraying are repeated, and after spraying, it is placed for 24 hours for curing.
[0028] The purpose of the present invention is to prepare titanium dioxide composite sol by a sol-gel method, which can be directly coated on plastics and other materials to obtain a super-hydrophilic anti-fog self-cleaning coating.
[0029] The present invention comprises the following steps:
[0030] 1. Preparation of silica sol
[0031] Silica sol was prepared by sol-gel method. 2 H 5 ) 4 , i.e. TEOS), 1 mol / L HNO 3 , deionized water, and anhydrous ethanol as raw materials. 3 :H 2 The solution was prepared in a ratio of HNO:EtOH = 1:0.005-0.1:3-10:5-20. First, TEOS and half the volume of anhydrous ethanol raw material were mixed evenly, stirred under magnetic force for 20 minutes, and then HNO 3 , H 2 After the mixture of TEOS and anhydrous ethanol is uniformly mixed, it is added dropwise to the mixture at room temperature, and the mixture is stirred in a sealed glass bottle for 6 hours to obtain a silica sol. After the sol is aged at 50°C for 1 to 7 days, the desired silica precursor sol is obtained.
[0032] 2. Preparation of titanium dioxide composite sol
[0033] The titanium dioxide composite sol is composed of a mixture of a titanium dioxide precursor sol and a silicon dioxide precursor sol, wherein the content of the titanium dioxide precursor sol is 20 to 80 mol%. In order to prepare a titanium dioxide precursor sol with better dispersibility and strong crystallinity, it is necessary to reasonably control the hydrolysis and crystallization process of the raw material titanate to avoid precipitation of the titanate during the hydrolysis process and incomplete hydrolysis affecting the subsequent crystallization. Here, a two-step strategy is used to prepare the titanium dioxide precursor sol. First, a titanium dioxide mother liquor is prepared by a hydrolysis process, and then a titanium dioxide nanocrystal suspension is obtained by a crystallization process. The classical sol-gel method is used to prepare tetrabutyl titanate (Ti(OCH 2 CH 2 CH 2 CH 3 ) 4 , TNBT) was mixed with deionized water, nitric acid and anhydrous ethanol to prepare titanium dioxide mother solution, and acetylacetone (C 5 H 8 O) as a stabilizer. TNBT:H 2 O:C 5 H 8 O:HNO 3 The molar ratio is 1:0.5-10:0.1-0.5:0.1, and the TNBT concentration in the solution is controlled to be 0.4M by adding anhydrous ethanol. First, TNBT and half volume of anhydrous ethanol are mixed evenly, and acetylacetone is added at the same time, and magnetic stirring is performed for 20 minutes. Then, under stirring conditions, the other half volume of anhydrous ethanol, water, and nitric acid mixture is added dropwise. After adding, stirring is continued for 6 hours, and then aged at room temperature for 2 days to obtain titanium dioxide mother solution.
[0034] The titanium dioxide mother liquor was then used to prepare titanium dioxide nanocrystalline sol. The preparation of the crystalline sol went through multiple steps. First, the titanium dioxide mother liquor was added dropwise into deionized water under stirring conditions to control the final H 2 The O / TNBT molar ratio is 50-400, and then the mixture is heated and refluxed at 90-100°C for 12 hours to produce TiO in the liquid phase. 2 The crystallization of particles requires constant stirring throughout the process to prevent the nanoparticles from aggregating and forming precipitation. After heating and refluxing, it is exchanged with anhydrous ethanol to remove water. The exchange process is to first remove most of the water by rotary evaporation to reduce the volume of the sol to about 20% of the original, and then dissolve it with anhydrous ethanol, repeat the rotary evaporation process 3 times to remove most of the water in the sol. Finally, it is diluted with anhydrous ethanol to a titanium dioxide solid content of 2-10%. In order to make the nanocrystals more stable and evenly dispersed in the solution, the solution is ultrasonically treated for 1 hour to obtain the desired titanium dioxide precursor sol. The final sol consists of TiO 2It is composed of nanocrystals. It will not gel and have obvious crystal aggregation, and can be placed at room temperature for a long time without crystal precipitation.
[0035] The titanium dioxide precursor sol is mixed with different amounts of silicon dioxide precursor sol, and stirred for 2 to 4 days to obtain the final titanium dioxide composite sol. Anhydrous ethanol is used as a diluent, and the solid content of the composite sol is controlled to be 0.8 to 8%.
[0036] 3. Preparation of titanium dioxide composite sol coating on the surface of various materials
[0037] The surfaces of different materials are cleaned with water and anhydrous ethanol several times, and then dried at room temperature. The substrates include glass sheets, eyeglass lenses, polyvinyl chloride, agricultural polyethylene films, commercial greenhouse films, polycarbonate, polyethylene terephthalate and other plastics. For various plastic substrates, vacuum plasma is first used for treatment before film formation. The treatment time is 5 minutes and the power is 200W. After treatment, the surface is obviously hydrophilic and the contact angle is less than 40°. The film can be formed by pulling, direct spraying, dripping, rolling and spin coating. After the solvent evaporates, the coating is obtained. The obtained coating is placed at room temperature for 24 hours to achieve stable curing. Heating conditions of 40 to 80°C can promote curing. The direct spraying method is preferred, which can achieve fast and large-area film processing. The air pressure used for spraying is 0.3MPa, and the spraying distance is 10 to 20cm. In order to make the spraying uniform, 2 to 10 cycles of back and forth spraying are selected to achieve uniform film formation on the substrate surface. After spraying, it is placed for 24 hours so that the surface and interior of the coating can be fully cured.
[0038] The titanium dioxide composite sol coating prepared by the present invention can be quickly coated on the surfaces of various materials such as glass and plastic to form a film, has a simple preparation process and good anti-fogging effect; the excellent performance of the coating is related to the content and existence form of the titanium dioxide component, and the titanium dioxide precursor sol obtained by our method has high dispersibility and better hydrophilicity; the titanium dioxide precursor sol can also form a mixed sol with metal oxides such as zirconium dioxide and aluminum oxide, which is used to form an anti-fogging self-cleaning coating on the surface of glass and plastic; before coating the titanium dioxide composite sol, the adhesion of the coating on the substrate can be improved by adding silicon dioxide or other organic intermediate layers such as organic silicon film and polyurethane film; the coating can be coated on the material surface by various methods such as scraping, rolling, pulling, spin coating and spraying, and the coating thickness can also be adjusted by multiple coatings to meet the needs of practical applications.
[0039] Tetrabutyl titanate can also be replaced by isopropyl titanate, titanium tetrachloride, titanyl sulfate and other raw materials.
[0040] The coating prepared by the present invention has the following advantages: (1) It can achieve super hydrophilic anti-fogging without UV pre-treatment, and the anti-fogging effect is stable. (2) It does not require high-temperature calcination and other conditions, and can be formed into a film by spraying and other methods, which is low in cost, simple in process, and more practical. (3) Compared with the anti-fogging treatment method of hydrophilic polymer coating, our method has strong water resistance and good weather resistance. It has good adhesion on the surface of various materials and is not easy to fall off.
[0041] The present invention has the following advantages:
[0042] The present invention uses a sol-gel method to prepare pre-crystallized titanium dioxide nanoparticles, which are mixed with silicon dioxide sol to obtain a composite sol, which can be formed into a film on the surface of glass and plastic substrate materials to obtain a porous structure coating. Since the titanium dioxide has been pre-crystallized and can be evenly dispersed in an aqueous solution, and has a large number of hydrophilic groups such as hydroxyl groups on the surface, there is no need for ultraviolet pretreatment and high-temperature calcination. After the coating is formed by spraying, pulling, roller coating and other methods, it has super-hydrophilic anti-fog self-cleaning performance and can be used on heat-sensitive plastic surfaces to avoid damage to the plastic caused by high-temperature treatment. The entire process has the advantages of low cost and large-area treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 A flow chart of an anti-fog self-cleaning titanium dioxide composite sol coating and a preparation method thereof;
[0044] Figure 2 The invention discloses an anti-fog self-cleaning titanium dioxide composite sol coating and a preparation method thereof, and a preparation reaction process of silicon dioxide sol;
[0045] Figure 3 The invention discloses an anti-fog self-cleaning titanium dioxide composite sol coating and a preparation method thereof, and a preparation reaction process of a titanium dioxide precursor sol;
[0046] Figure 4 This is a contact angle test diagram of an anti-fog self-cleaning titanium dioxide composite sol coating and a preparation method thereof before glass treatment in Example 1;
[0047] Figure 5 This is a contact angle test diagram of an anti-fog self-cleaning titanium dioxide composite sol coating and a preparation method thereof after glass treatment in Example 1;
[0048] Figure 6 This is a scanning electron microscope test image of the surface of the glass after treatment in Example 1 of an anti-fog self-cleaning titanium dioxide composite sol coating and a preparation method thereof, with a scale of 500 nm;
[0049] Figure 7It is a light transmittance curve of the PE film before and after treatment in Example 2 of an anti-fog self-cleaning titanium dioxide composite sol coating and a preparation method thereof;
[0050] Figure 8 This is a diagram of the anti-fog test of the PET film in Example 3 of an anti-fog self-cleaning titanium dioxide composite sol coating and a preparation method thereof;
[0051] Fig. 9 It is a curve diagram of the degradation effect of Rhodamine B on the PET film after being treated in Example 3 of an anti-fog self-cleaning titanium dioxide composite sol coating and its preparation method. DETAILED DESCRIPTION
[0052] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0053] Example 1
[0054] like Figure 1 As shown, an anti-fog self-cleaning titanium dioxide composite sol coating and a preparation method thereof, comprising the following steps:
[0055] S1. Preparation of silica sol Figure 2 As shown, under the catalysis of nitric acid, tetraethyl silicate undergoes hydrolysis and condensation to obtain the corresponding sol. The specific method is as follows:
[0056] The composition of silica sol is TEOS:HNO3:H 2 O:EtOH=1:0.01:5:8. First, mix TEOS and half volume of anhydrous ethanol raw material evenly, stir under magnetic force for 20min, and then add HNO 3 , H 2 After the mixture of TEOS and anhydrous ethanol is uniformly mixed, it is added dropwise into the mixture of TEOS and anhydrous ethanol at room temperature, and the mixture is stirred continuously for 6 hours in a sealed glass bottle to obtain a silica sol; after the sol is aged at 50°C for 2 days, the desired silica precursor sol is obtained.
[0057] S2. Preparation of titanium dioxide composite sol. The preparation reaction process is as follows: Figure 3 As shown:
[0058] The titanium dioxide composite sol is composed of a mixture of a titanium dioxide precursor sol and a silicon dioxide precursor sol, wherein the content of the titanium dioxide precursor sol is 40 mol % and the content of the silicon dioxide precursor sol is 60 mol %.
[0059] The titanium dioxide precursor sol was prepared by a two-step strategy. First, the titanium dioxide mother solution was prepared by a hydrolysis process, and then the titanium dioxide nanocrystal suspension was obtained by a crystallization process. Tetrabutyl titanate (Ti(OCH 2 CH 2 CH 2 CH 3 ) 4 , TNBT) was mixed with deionized water, nitric acid and anhydrous ethanol to prepare titanium dioxide mother solution, and acetylacetone (C 5 H 8 O) as a stabilizer. The TNBT concentration in the solution was controlled to be 0.4 M, TNBT:H 2 O:C 5 H 8 O:HNO 3 The molar ratio is 1:1:0.3:0.1. First, TNBT and half volume of anhydrous ethanol are mixed evenly, and acetylacetone is added at the same time, and magnetic stirring is performed for 20 minutes. Then, under stirring conditions, the other half volume of anhydrous ethanol, water, and nitric acid mixture is added dropwise. After adding, stirring is continued for 6 hours, and then aged at room temperature for 2 days to obtain titanium dioxide mother solution.
[0060] The titanium dioxide mother liquor was then used to prepare titanium dioxide nanocrystalline sol. The preparation of the crystalline sol went through multiple steps. First, the titanium dioxide mother liquor was added dropwise into deionized water under stirring conditions to control the final H 2 The O / TNBT molar ratio was 100, and then the mixture was heated and refluxed at 90-100 °C for 12 hours to produce TiO 2 The crystallization of particles requires constant stirring throughout the process to prevent the nanoparticles from agglomerating and forming precipitation. After heating and refluxing, it is exchanged with anhydrous ethanol to remove water. The exchange process is to first remove most of the water by rotary evaporation to reduce the volume of the sol to about 20% of the original volume, and then dissolve it with anhydrous ethanol. Repeat the rotary evaporation process 3 times to remove most of the water in the sol. Finally, it is diluted with anhydrous ethanol to a titanium dioxide solid content of 5%. In order to make the nanocrystals more stable and evenly dispersed in the solution, the solution is ultrasonically treated for 1 hour to obtain the desired titanium dioxide precursor sol. The final sol consists of TiO 2 It is composed of nanocrystals. It will not gel and have obvious crystal aggregation, and can be placed at room temperature for a long time without crystal precipitation.
[0061] The titanium dioxide precursor sol was mixed with different amounts of silicon dioxide precursor sol and stirred for 2 days to obtain the final titanium dioxide composite sol. After being diluted with anhydrous ethanol, the solid content of the composite sol was controlled to be 1%.
[0062] S3. Preparation of titanium dioxide composite sol coating on glass surface
[0063] The pathological grade glass slide was cleaned with water and anhydrous ethanol several times, and then dried at room temperature. The coating was formed by spraying. The spraying pressure was 0.3MPa, and the spraying distance was 20cm. In order to make the spraying uniform, 4 cycles of back and forth spraying were selected to achieve uniform film formation on the substrate surface. After spraying, it was left for 24 hours to allow the coating surface and interior to be fully cured.
[0064] (4) Effect after implementation
[0065] The coated glass is super hydrophilic, and the contact angle before spraying the coating is as Figure 4 As shown, the contact angle is 29.1±1.2°. After spraying the coating, the contact angle is as follows Figure 5 As shown in Figure 2, the contact angle is less than 5°. After spraying the coating, the surface has an obvious nanostructure. The nanostructure can be seen from Figure 6 observed in scanning electron microscopy.
[0066] Example 2
[0067] like Figure 1 As shown, an anti-fog self-cleaning titanium dioxide composite sol coating and a preparation method thereof, comprising the following steps:
[0068] S1. Preparation of silica sol Figure 2 As shown, under the catalysis of nitric acid, tetraethyl silicate undergoes hydrolysis and condensation to obtain the corresponding sol. The specific method is as follows:
[0069] The composition of silica sol is TEOS:HNO 3 :H 2 O:EtOH=1:0.02:5:10. First, mix TEOS and half volume of anhydrous ethanol raw material evenly, stir under magnetic force for 20min, and then add HNO 3 , H 2 After the mixture of TEOS and anhydrous ethanol is uniformly mixed, it is added dropwise to the mixture at room temperature, and the mixture is stirred in a sealed glass bottle for 6 hours to obtain a silica sol. After the sol is aged at 50°C for 2 days, the desired silica precursor sol is obtained.
[0070] S2. Preparation of titanium dioxide composite sol. The preparation reaction process is as follows: Figure 3 As shown:
[0071] The titanium dioxide composite sol is composed of a mixture of a titanium dioxide precursor sol and a silicon dioxide precursor sol, wherein the titanium dioxide precursor sol content is 50 mol% and the silicon dioxide precursor sol content is 50 mol%. The titanium dioxide precursor sol is prepared by a two-step strategy, firstly, a hydrolysis process is used to prepare a titanium dioxide mother solution, and then a crystallization process is used to obtain a titanium dioxide nanocrystal suspension. The sol-gel method is used to prepare tetrabutyl titanate (Ti(OCH 2 CH 2 CH 2 CH 3 ) 4 , TNBT) was mixed with deionized water, nitric acid and anhydrous ethanol to prepare titanium dioxide mother solution, and acetylacetone (C 5 H 8 O) as a stabilizer. The TNBT concentration in the solution was controlled to be 0.4 M, TNBT:H 2 O:C 5 H 8 O HNO 3 The molar ratio is 1:2:0.2:0.1. First, TNBT and half volume of anhydrous ethanol are mixed evenly, and acetylacetone is added at the same time, and magnetic stirring is performed for 20 minutes. Then, under stirring conditions, the other half volume of anhydrous ethanol, water, and nitric acid mixture is added dropwise. After adding, stirring is continued for 6 hours, and then aged at room temperature for 2 days to obtain titanium dioxide mother solution.
[0072] The titanium dioxide mother liquor was then used to prepare titanium dioxide nanocrystalline sol. The preparation of the crystalline sol went through multiple steps. First, the titanium dioxide mother liquor was added dropwise into deionized water under stirring conditions to control the final H 2 The O / TNBT molar ratio was 200, and then the mixture was heated and refluxed at 90-100 °C for 12 hours to produce TiO 2 The crystallization of particles requires constant stirring throughout the process to prevent the nanoparticles from agglomerating and forming precipitation. After heating and refluxing, it is exchanged with anhydrous ethanol to remove water. The exchange process is to first remove most of the water by rotary evaporation to reduce the volume of the sol to about 20% of the original volume, and then dissolve it with anhydrous ethanol. Repeat the rotary evaporation process 3 times to remove most of the water in the sol. Finally, it is diluted with anhydrous ethanol to a titanium dioxide solid content of 5%. In order to make the nanocrystals more stable and evenly dispersed in the solution, the solution is ultrasonically treated for 1 hour to obtain the desired titanium dioxide precursor sol. The final sol consists of TiO 2 It is composed of nanocrystals. It will not gel and have obvious crystal aggregation, and can be placed at room temperature for a long time without crystal precipitation.
[0073] The titanium dioxide precursor sol was mixed with different amounts of silicon dioxide precursor sol and stirred for 3 days to obtain the final titanium dioxide composite sol. After being diluted with anhydrous ethanol, the solid content of the composite sol was controlled to be 1.2%.
[0074] S3. Preparation of titanium dioxide composite sol coating on the greenhouse film surface
[0075] The greenhouse film (PE) was cleaned with water and anhydrous ethanol several times, and then dried at room temperature. Then plasma treatment was carried out, the treatment time was 5min, the power was 200W, and the contact angle after treatment was 34.2±2.5°. Finally, the coating was formed by spraying. The spraying pressure was 0.3MPa, and the spraying distance was 20cm. In order to make the spraying uniform, 4 cycles of back and forth spraying were selected to achieve uniform film formation on the substrate surface. After spraying, it was left for 24h to allow the coating surface and interior to be fully cured.
[0076] Effect after implementation
[0077] The PE film with coating is super hydrophilic, with a contact angle of up to 103.1±1.6° before spraying the coating and less than 5° after spraying the coating. At the same time, the coating can improve the light transmittance of the PE film. Figure 7 As shown, the light transmittance can be improved by 5% overall, wherein the dotted line represents the PE film before treatment, and the solid line is the light transmittance curve of the PE film after treatment.
[0078] Example 3
[0079] like Figure 1 As shown, an anti-fog self-cleaning titanium dioxide composite sol coating and a preparation method thereof, comprising the following steps:
[0080] S1. Preparation of silica sol Figure 2 As shown, under the catalysis of nitric acid, tetraethyl silicate undergoes hydrolysis and condensation to obtain the corresponding sol. The specific method is as follows:
[0081] The composition of silica sol is TEOS:HNO 3 :H 2 O:EtOH=1:0.02:5:10. First, mix TEOS and half volume of anhydrous ethanol raw material evenly, stir under magnetic force for 20min, and then add HNO 3 , H 2 After the mixture of TEOS and anhydrous ethanol is uniformly mixed, it is added dropwise to the mixture at room temperature, and the mixture is stirred in a sealed glass bottle for 6 hours to obtain a silica sol. After the sol is aged at 50°C for 2 days, the desired silica precursor sol is obtained.
[0082] S2. Preparation of titanium dioxide composite sol. The preparation reaction process is as follows: Figure 3 As shown:
[0083] The titanium dioxide composite sol is composed of a mixture of a titanium dioxide precursor sol and a silicon dioxide precursor sol, wherein the titanium dioxide precursor sol content is 60 mol% and the silicon dioxide precursor sol content is 40 mol%. The titanium dioxide precursor sol is prepared by a two-step strategy, firstly, a hydrolysis process is used to prepare a titanium dioxide mother solution, and then a crystallization process is used to obtain a titanium dioxide nanocrystal suspension. The sol-gel method is used to prepare tetrabutyl titanate (Ti(OCH 2 CH 2 CH 2 CH 3 ) 4 , TNBT) was mixed with deionized water, nitric acid and anhydrous ethanol to prepare titanium dioxide mother solution, and acetylacetone (C 5 H 8 O) as a stabilizer. The TNBT concentration in the solution was controlled to be 0.4 M, TNBT:H 2 O:C 5 H 8 O:HNO 3 The molar ratio is 1:2:0.1:0.1. First, TNBT and half volume of anhydrous ethanol are mixed evenly, and acetylacetone is added at the same time, and magnetic stirring is performed for 20 minutes. Then, under stirring conditions, the other half volume of anhydrous ethanol, water, and nitric acid mixture is added dropwise. After adding, stirring is continued for 6 hours, and then aged at room temperature for 2 days to obtain titanium dioxide mother solution.
[0084] The titanium dioxide mother liquor was then used to prepare titanium dioxide nanocrystalline sol. The preparation of the crystalline sol went through multiple steps. First, the titanium dioxide mother liquor was added dropwise into deionized water under stirring conditions to control the final H 2 The O / TNBT molar ratio was 200, and then the mixture was heated and refluxed at 90-100 °C for 12 hours to produce TiO 2 The crystallization of particles requires constant stirring throughout the process to prevent the nanoparticles from agglomerating and forming precipitation. After heating and refluxing, it is exchanged with anhydrous ethanol to remove water. The exchange process is to first remove most of the water by rotary evaporation to reduce the volume of the sol to about 20% of the original, and then dissolve it with anhydrous ethanol. The rotary evaporation process is repeated 3 times to remove most of the water in the sol. Finally, it is diluted with anhydrous ethanol to a titanium dioxide solid content of 6%. In order to make the nanocrystals more stable and evenly dispersed in the solution, the solution is ultrasonically treated for 1 hour to obtain the desired titanium dioxide precursor sol. The final sol consists of TiO 2 It is composed of nanocrystals. It will not gel and have obvious crystal aggregation, and can be placed at room temperature for a long time without crystal precipitation.
[0085] The titanium dioxide precursor sol was mixed with different amounts of silicon dioxide precursor sol and stirred for 3 days to obtain the final titanium dioxide composite sol. After being diluted with anhydrous ethanol, the solid content of the composite sol was controlled to be 1.2%.
[0086] S3. Preparation of titanium dioxide composite sol coating on polyethylene terephthalate film surface
[0087] The polyethylene terephthalate (PET) film was cleaned with water and anhydrous ethanol several times, and then dried at room temperature. Subsequently, plasma treatment was performed, with a treatment time of 5 minutes and a power of 200W. The contact angle after treatment was 24.5±2.2°. Finally, the coating was formed by spraying. The spraying pressure was 0.3MPa, and the spraying distance was 20cm. In order to make the spraying uniform, 6 cycles of back and forth spraying were selected to achieve uniform film formation on the substrate surface. After spraying, it was left for 24 hours to allow the coating surface and interior to be fully cured.
[0088] Effect after implementation
[0089] The coated PET film is super hydrophilic with a contact angle of less than 5°, thus having a significant anti-fogging effect. Figure 8 As shown in the figure, the PET with coating on the right side remains clear and does not fog up in hot water at 60°C. Photocatalytic test with Rhodamine B shows that after UV treatment, the concentration of Rhodamine B can be significantly reduced, as shown in the figure below. Fig. 9 As shown, it means that the coating also has good photocatalytic self-cleaning performance.
[0090] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. An anti-fog self-cleaning titanium dioxide composite sol coating, characterized in that: The titanium dioxide composite sol is pulled or directly sprayed or dripped or rolled or spin-coated on the surface of the plastic substrate to form a film, and the titanium dioxide composite sol coating is obtained after the solvent evaporates; The titanium dioxide composite sol comprises a titanium dioxide precursor sol and a silicon dioxide precursor sol in a molar ratio of (3-7): (3-7), and a solid content of 0.8-8%; The plastic substrate includes any one of the following: glass sheets, eyeglass lenses, polyvinyl chloride films, agricultural polyethylene films, commercial greenhouse films, polycarbonate films and polyethylene terephthalate films.
2. The anti-fog self-cleaning titanium dioxide composite sol coating according to claim 1, characterized in that: The titanium dioxide precursor sol is composed of TiO2 nanocrystals with a diameter of 5 to 30 nm.
3. The anti-fog self-cleaning titanium dioxide composite sol coating according to claim 1, characterized in that: Or the titanium dioxide composite sol comprises a titanium dioxide precursor sol and a metal oxide, and the metal oxide is zirconium dioxide or aluminum oxide; Alternatively, silicon dioxide or an organic intermediate layer is added to the titanium dioxide composite sol to improve the adhesion of the coating on the plastic substrate, and the organic intermediate layer is an organic silicon film or a polyurethane film.
4. The method for preparing an anti-fog self-cleaning titanium dioxide composite sol coating according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, using tetraethyl silicate, HNO3, deionized water, and anhydrous ethanol in a molar ratio of 1:0.005-0.1:3-10:5-20 to prepare a silica sol, and aging the silica sol at 50° C. for 1-7 days to obtain the silica precursor sol; S2, using titanium compound, deionized water, nitric acid, anhydrous ethanol and a stabilizer to prepare a titanium dioxide mother solution, wherein the molar ratio of the titanium compound, deionized water, stabilizer and nitric acid is 1:0.5-10:0.1-0.5:0.1, and anhydrous ethanol is used to control the concentration of the titanium compound in the titanium dioxide mother solution; The titanium dioxide mother solution is added dropwise into deionized water under stirring conditions, and the final molar ratio of deionized water to the titanium compound is controlled to be 50-400, and then the mixture is continuously heated under reflux and stirred for 12 hours to generate crystals of TiO2 particles in the liquid phase, and then the water is exchanged with anhydrous ethanol to remove the water, and the mixture is diluted to a specified concentration to obtain the titanium dioxide precursor sol; The titanium dioxide precursor sol and the titanium dioxide precursor sol are mixed and stirred at a molar ratio of (3-7): (3-7) to obtain a titanium dioxide composite sol, and anhydrous ethanol is used as a diluent to adjust the solid content of the titanium dioxide composite sol to 0.8-8%; S3, cleaning and drying the plastic substrate, and then treating it with vacuum plasma, forming a film by pulling, direct spraying, dripping, rolling or spin coating, and obtaining a coating after the solvent evaporates, and heating and curing at 40-80° C. to obtain the titanium dioxide composite sol coating.
5. The method for preparing an anti-fog self-cleaning titanium dioxide composite sol coating according to claim 4, characterized in that: In step S1, when preparing the silica sol, tetraethyl silicate and half volume of anhydrous ethanol are first mixed evenly, and stirred under magnetic force for 20 minutes to obtain a tetraethyl silicate anhydrous ethanol mixed solution; then HNO3, deionized water and the other half volume of anhydrous ethanol are mixed evenly, and then added dropwise to the tetraethyl silicate anhydrous ethanol mixed solution at room temperature, and the silica sol is obtained after continuous stirring in a sealed glass bottle for 6 hours.
6. The method for preparing an anti-fog self-cleaning titanium dioxide composite sol coating according to claim 4, characterized in that: In step S2, the titanium compound is tetrabutyl titanate or isopropyl titanate or titanium tetrachloride or titanyl sulfate, the stabilizer is acetylacetone, and the concentration of the titanium compound in the titanium dioxide mother liquor is 0.4M; First, the titanium compound and half volume of anhydrous ethanol are mixed evenly, and acetylacetone is added at the same time. After magnetic stirring for 20 minutes, the other half volume of anhydrous ethanol, water, and nitric acid mixture is added dropwise under stirring conditions; stirring is continued for 6 hours after the addition, and then aged at room temperature for 2 days to obtain the titanium dioxide mother solution; The heating reflux temperature is 90-100°C; The method of exchanging and removing water with anhydrous ethanol is as follows: first, remove part of the water by rotary evaporation to reduce the volume of the TiO2 sol to 20% of the original volume, then dissolve it with anhydrous ethanol, and repeat the rotary evaporation process for 3 times; The specified concentration is: titanium dioxide solid content 2 to 10%; The titanium dioxide precursor sol is mixed with the titanium dioxide precursor sol and then diluted with anhydrous ethanol so that the solid content of the titanium dioxide composite sol is 0.8-8%.
7. The method for preparing an anti-fog self-cleaning titanium dioxide composite sol coating according to claim 4, characterized in that: In step S3, the vacuum plasma treatment time is 5 minutes and the power is 200 W; after the vacuum plasma treatment, the contact angle of the glass substrate is less than 40°; The coating curing conditions are: leaving at room temperature for 24 hours.
8. The method for preparing an anti-fog self-cleaning titanium dioxide composite sol coating according to claim 4, characterized in that: In step S3, the spraying pressure is 0.3 MPa, the spraying distance is 10 to 20 cm, and the spraying is repeated for 2 to 10 cycles. After spraying, the material is left to stand for 24 hours for curing.
Citation Information
Patent Citations
Method for preparing self-cleaning antifogging coating film
CN102718410A
Antifouling self-cleaning aluminum foil for air conditioner heat exchanger fins and preparation method of antifouling self-cleaning aluminum foil
CN118530608A
Cited By
Organic-inorganic hybrid wear-resistant antifogging coating, preparation method and application thereof, and organic-inorganic hybrid wear-resistant antifogging coating
CN119775812A
Nanometer super-hydrophilic self-cleaning wear-resistant anti-fog film material, optical lens and preparation method of nanometer super-hydrophilic self-cleaning wear-resistant anti-fog film material
CN122168055A
